Editorial introduction to thematic section: Papers from the Excellence Network of Island Territories (RETI) meetings, Orkney, June 2015 - James E. Randall (Island Studies Journal, 2016)
This guest editorial introduces the thematic section of papers, earlier drafts of which had been presented at the RETI meetings held at Orkney College, University of the Highlands and Islands, Scotland, in June 2015.